Medicinal plants used by inhabitants of the Shigar Valley, Baltistan region of Karakorum range-Pakistan - Zaheer Abbas; Shujaul Mulk Khan; Jan Alam; Sher Wali Khan; Arshad Mehmood Abbasi (BMC, 2017)
Abstract Background The inhabitants of mountainous terrains depend on folk therapies to treat various ailments; however lack of plant based research and geographical constraints set the traditional knowledge in jeopardy. Present study is the first documentation on traditional uses of plant species by the inhabitants of the Shigar Valley, Karakorum Range, Northern Pakistan. Method Ethnobotanical data were collected over a period from July, 2013 to October, 2016 from 84 respondents, using semi structured questionnaire. Quantitative indices such as relative frequency citation (RFCs) and fidelity level (FL) were intended to evaluate the importance of medicinal plant species. Results In total 84 plant species belonging to 36 families and 72 genera were recorded. Fabaceae was dominant with 7 species, followed by Asteraceae, Lamiaceae and Rosacea (6 species each). Leaves, root, flowers, seeds and fruits were the frequently utilized plant parts, whereas among drug formulations, decoction (49%) was ranked first. Majority of the plant species were used to treat abdominal, respiratory and dermal ailments (31, 12 and 12, respectively). RFCs value ranged 0.477 to 0.11 for Tanacetum falconeri and Allium carolinianum, respectively; while Hippophe rhamnoides and Thymus linearis depicted 100% FL. Comparative assessment with previous reports revealed that traditional uses of 26% plant species counting Hedyserum falconeri, Aconitum violoceum var. weileri, Arnebia guttata, Biebersteinia odora, Clematis alpine var. sibirica, Corydalis adiantifolia and Saussurea simpsoniana were reported for the first time. Conclusion The endemic medicinal plant species and traditional knowledge of Balti community living in extremely high mountains area were explored for the first time. A comprehensive survey of this region could be significant to drive the existing knowledge in market circuit with sustainable collection, and to evaluate economic potential of the plant species. Additionally, social livelihood could be reinforced through establishing collection sites, transformation and drying centres for micro and macro marketing of medicinal plant species. Graphical abstract Plants and people interaction in the Karakorum Mountains